Integrasi BBR dalam Pengembangan Materi Ajar Pengantar Pendidikan untuk Penguatan Karakter Mahasiswa - Muhammad Radian Nur Alamsyah; Sri Haryati (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2021)
Abstract: This study aims to develop teaching materials for the Introduction to Education course by integrating BBR designs in an effort to strengthen student character. This study uses the Research & Development (R&D) method with the approach of Borg & Gall. The product validation process is carried out by means of expert judgment. Data collection using a Likert scale questionnaire with 4 response options. The data analysis process was carried out in a descriptive qualitative manner. This research produces teaching material products with an average percentage of achievement in all aspects of 80.54%, which is categorized as good. Thus, this product can be an alternative teaching material in the Introduction to Education course that has integrated the BBR design, so that it has the potential to strengthen the character of students.